Three essays on regional economic development - Deming, Kristopher, author; Weiler, Stephan, advisor; Barbier, Edward, committee member; Pena, Anita, committee member; Thilmany, Dawn, committee member (Colorado State University. Libraries, 2022)
This dissertation explores factors that contribute to regional economic growth. The first two chapters focus on one of the key drivers of regional economic growth: entrepreneurship. In the first two chapters I examine how the Earned Income Tax Credit (EITC) contributes to entrepreneurship. Chapter 1 focuses on the labor demand side of regional entrepreneurship, finding the introduction of state EITC policies reduces the number of new establishments and the number of establishment expansions relative to counties in states without such a policy. In Chapter 2, at the individual level, I find that increasing the amount of the EITC increases the likelihood that the child of the credit recipient becomes a business owner as an adult. The third chapter focuses directly on what caused economic growth in Pre-Colonial India. I propose that the introduction of a New World crop, a form of an agricultural productivity shock, caused economic growth in India. I find that the introduction of maize did contribute to economic growth in Pre-Colonial India.